2011
DOI: 10.1534/genetics.110.121327
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Flowering Time Genes to Sunflower Domestication and Improvement

Abstract: Determining the identity and distribution of molecular changes leading to the evolution of modern crop species provides major insights into the timing and nature of historical forces involved in rapid phenotypic evolution. In this study, we employed an integrated candidate gene strategy to identify loci involved in the evolution of flowering time during early domestication and modern improvement of the sunflower (Helianthus annuus). Sunflower homologs of many genes with known functions in flowering time were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 151 publications
1
75
0
Order By: Relevance
“…Because c4973 had been sequenced previously only on a small sample of American landraces, we obtained additional sequences from our diversity panel to sample c4973 sequence diversity more thoroughly in North American landraces (Tables S1 and S5). Sequence data for seven putative neutral loci were obtained for a previously published study of this diversity panel (Table S5) (31). HaFT1 PCR products were digested with BstEII to genotype individuals for the frameshift mutation nearly fixed in domesticated haplotypes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because c4973 had been sequenced previously only on a small sample of American landraces, we obtained additional sequences from our diversity panel to sample c4973 sequence diversity more thoroughly in North American landraces (Tables S1 and S5). Sequence data for seven putative neutral loci were obtained for a previously published study of this diversity panel (Table S5) (31). HaFT1 PCR products were digested with BstEII to genotype individuals for the frameshift mutation nearly fixed in domesticated haplotypes.…”
Section: Methodsmentioning
confidence: 99%
“…An 885-bp portion of the gibberellin 2-oxidase homolog HaGA2ox was examined as part of an ongoing study of a genetic diversity panel from the United States and Canada (31). This panel included 18 individuals from improved modern crop lines, 19 individuals from Native American landraces, and 23 individuals from a geographically diverse sample of wild sunflower populations (Table S1).…”
Section: Selection On Gibberellin 2-oxidase Homolog Haga2ox During Earlymentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis, under long days, GI acts earlier in the pathway than CONSTANS (CO) and FLOWERING TIME (FT), by increasing the CO and FT mRNA abundance. CO and FT were targets of selection during domestication of crops such as rice (Takahashi and Shimamoto, 2011;Wu et al, 2013) and sunflower (Helianthus annuus; Blackman et al, 2011). In pea (Pisum sativum), Hecht et al (2007) identified LATE BLOOMER1 (LATE1) as the pea ortholog of Arabidopsis GI and showed that LATE1 is necessary for the promotion of flowering, the production of a mobile flowering stimulus, and the induction of an FT homolog under long-day conditions.…”
Section: Selectionmentioning
confidence: 99%
“…The TE-mediated duplication of the tomato SUN gene described above provides one such example. Another well documented instance involves paralogous copies of the flowering time gene FT ( FLOWERING LOCUS T) in sunflower and selection for changes in flowering time during domestication and later crop improvement (Blackman et al, 2010, 2011). FT genes function as positive regulators of reproductive meristem development, and Blackman and colleagues were able to identify four paralogous copies in sunflower, three of which appear to be functional and show evidence of having played a role in a shift toward later flowering time during sunflower domestication.…”
Section: Genetic Basis Of Domestication Phenotypesmentioning
confidence: 99%